Implementasi Moderasi Pendidikan Islam Rahmatallil ’Alamin dengan Nilai-Nilai Islam - Hamdi Abdul Karim (Pascasarjana IAIN Metro, 2019)
The moderation of Islamic education has given birth to a great civilization with an extraordinary spectrum that astonishes the world. The rules of the value of Islamic teachings that display moderation in its most beautiful format have made it very easily accepted by every human layer. Moderation in Islam has given a